Expanding the scope and visibility of ambulatory stewardship programs with novel coronavirus disease 2019 (COVID-19) therapeutics - Hongkai Bao; Yi Guo; Mei H. Chang; Terrence McSweeney; Austin M. Golia; Kelsie Cowman; Rachel Bartash; Brenda I. Anosike; Priya Nori (Cambridge University Press, 2022)
Antimicrobial stewardship programs (ASPs) can be expanded to the outpatient setting to serve as a first line of defense against coronavirus disease 19 (COVID-19) hospitalizations and to reduce the burden on emergency departments and acute-care hospitals. Given the numerous emergency use authorizations of monoclonal antibodies and oral antivirals, ASPs possess the expertise and leadership to direct ambulatory COVID-19 initiatives and transform it into a predominantly outpatient illness. In this review, we summarize the critical role and benefits of an ASP-championed ambulatory COVID-19 therapeutics program.